Prevalence and associated risk factors for Kaposi’s sarcoma among HIV-positive patients in a referral hospital in Northern Tanzania: a retrospective hospital-based study - George P. Semango; Renard M. Charles; Consolata I. Swai; Alex Mremi; Patrick Amsi; Tolbert Sonda; Elichilia R. Shao; Daudi R. Mavura; Leo A. B. Joosten; Elingarami Sauli; Mramba Nyindo (BMC Cancer, 2018)
Abstract Background Kaposi’s sarcoma (KS) is a multifocal angioproliferative tumor involving blood and lymphatic vessels, caused by Human Herpes Virus-8 (HHV-8). KS is an important AIDS-defining tumor with high prevalence in Sub-Saharan Africa, including Tanzania which has high HIV and HHV-8 sero-prevalence. It is critically important to monitor the prevalence of AIDS-defining tumors, such as KS, in the age of HIV/AIDS. We studied the prevalence of KS and associated risk factors among HIV-positive patients at Kilimanjaro Christian Medical Centre (KCMC), a referral hospital in northern Tanzania, over the period from January 2012 to December 2015. Methods This was a retrospective hospital-based cross-sectional study to determine the prevalence of KS among HIV/AIDS patients between 2012 and 2015. The study included 1100 HIV patients’ data which were collected at the Infectious Disease Clinic (IDC) from patients’ files. Stata version 13 (StataCorp LP, Texas 77,845 USA) was used for all statistical analyses. The prevalence of KS was calculated across levels of a number of categorical variables. Logistic regression was performed to determine relative risk of KS for all characteristics. We included all variables with p-values ≤10% in the multivariate analysis, including ART use, as this is considered to have an influence on KS. In the multivariate analysis, statistical significance was established based on a two-tailed p-value ≤5%. All patients’ notes were kept confidential as per the Helsinki declaration. Results Our results revealed a 4.6% prevalence of KS at KCMC hospital, between January 2012 and December 2015, 51(4.6%) patients were diagnosed with KS out of 1100 HIV-positive patients. The study further revealed that KS in HIV patients was most associated with low CD4 cell count (less than or equal to 200 cells/μl). Moreover, women were more likely than men to diagnosed with KS, with higher odds significantly associated with KS (OR 0.42, p < 0.009). Increased age, above 35 years, among the HIV seropositive patients was significantly associated with KS (OR 25.67, p < 0.007). HIV patients who were none smokers were more likely to suffer from KS compared to HIV smokers (OR 0.41, p < 0.010). Conclusion KS remains a common malignant vascular tumor commonly associated with HIV/AIDS in Tanzania. Our study highlights the need for continued efforts to combat HIV, as well as associated diseases such as KS. Continued availability of ART (Anti-Retroviral Therapy) to HIV/AIDS patients, and test reagents for CD4 cell count and viral load determination are important measures to alleviate the suffering of these patients. Furthermore, studies to gather more evidence on ART resistance are highly needed to guide treatment choices.